TOTAL QUALITY MANAGEMENT - KUMAR S DR (NEW DELHI UNIVERSITY SCIENCE PRESS LAXMI PUBLICATIONS PVT LTD, 2011)
S. Kumar's "Total Quality Management" offers a comprehensive and accessible guide to the principles, practices, and tools essential for fostering a culture of continuous improvement within an organization. The book is structured to cater to both students of management and industry professionals, providing a solid foundation in the philosophy of TQM and a practical toolkit for its implementation.
QUALITY MANAGEMENT
BBA & MBA
Keywords: QUALITY MANAGEMENT; MANAGEMENT